Information models for product representation: core and assembly models. (28th June 2005) - Rachuri, Sudarsan; Baysal, Mehmet; Roy, Utpal; Foufou, Sebti; Bock, Conrad; Fenves, Steven; Subrahmanian, Eswaran; Lyons, Kevin; Sriram, Ram
We present an integrated view of two information models developed at NIST and their use. The Core Product Model (CPM) provides a generic model of the artifact's function, form and behaviour. The Open Assembly Model (OAM) defines a system level conceptual model of assemblies supporting tolerance and kinematics representation. The objectives of the paper are to: present recent extensions of the two models; explicitly link the two models; and propose CPM/OAM as the basis of a product information-modelling framework for Product Lifecycle Management (PLM). A case study illustrates the use of CPM/OAM for capturing information.